FROM ANCIENT TRADITIONS TO MODERN GREATNESS: THE DEVELOPMENT OF THE TEXTILE INDUSTRY OF UZBEKISTAN - Yormatov Ilmidin Toshmatovich (American Journals, 2023)
As one of the largest textile production bases in Central Asia, Uzbekistan has made significant progress in the development and improvement of the textile industry in recent years. After the arrival of new leadership in the country in 2016, the textile industry became one of the main priorities for the development of the economy of Uzbekistan. In this article, the main points of the development of the textile industry in the new Uzbekistan were considered.
Keywords: Industry, export, light industry, textile industry, joint venture, investment, economy, cluster.